Variability of White Spot Syndrome Virus (WSSV) envelope protein VP28 from diseased shrimp (Litopenaeus vannamei) in Indonesia - Tasakka, A.C.M.A.R.; Latama, G.; Hidayani, A.A.; Parenrengi, A.; Tenriulo, A.; Relatami, A.N.R.; Moore, A.M.; Shaheen, A. (Penerbit Universiti Kebangsaan Malaysia, 2022)
White Spot Disease (WSD) is a viral disease affecting crustaceans. Caused by the White Spot Syndrome Virus (WSSV), this disease has caused significant mortality in commercially cultivated marine shrimp species with severe impacts on the shrimp farming industry and may be a threat to wild shrimp stocks. Thorough studies on the molecular biology of this pathogen are urgently needed to improve understanding of the virus at a molecular level, including variation in key viral protein (VP) components of the WSSV virion. This study aimed to isolate and characterize WSSV VP28 gene encoding envelope proteins from Indonesian Pacific white shrimp (Litopenaeus vannamei) isolates. Infected juvenile shrimp were collected from Pangkep, Barru, and Pinrang Districts in South Sulawesi, Indonesia. Genomic DNA was isolated from infected shrimp muscle tissue using a DTAB-CTAB (dodecyle trimethyl ammonium bromide-hexadecyl trimethyl ammonium bromide) DNA extraction procedure. The WSSV VP28 DNA sequences from Pangkep, Barru, and Pinrang isolates were 640-680 bp in length. Homology of Pangkep isolates with isolates from Barru and Pinrang was 97-99%. BLAST-N (Basic Local Alignment Search Tool-Nucleotide) analysis showed isolates from all three sites clustered with WSSV VP28 accessions from China, Indonesia, Japan, South Carolina and Vietnam. These results increase the geographic spread and host taxon coverage of WSSV VP28 sequence data for Indonesia.